Lifetime exposure to traumatic events among adolescents in contact with the Nigerian juvenile justice systems compared with a comparison group of secondary school students. (May 2014) - Atilola, Olayinka; Omigbodun, Olayinka; Bella-Awusah, Tolulope
Abstract : Background: There are some knowledge gaps in what is known about pre-contact exposure to traumatic events among adolescents within the juvenile justice system. Data often focus on psychological sequelae without describing the traumatic events. In addition, there are few data from sub-Saharan Africa where juvenile justice inmates are often minor offenders and may themselves have been victims of abuse and neglect. Objective: To present detailed data on the lifetime prevalence rate and pattern of traumatic events among a cohort of adolescents in juvenile justice custody in Nigeria and to compare inmates who are 'offenders' with those who are 'victims'. Methods: Inmates of a borstal and a remand home comprised the study group and age- and gender-matched adolescents from two government schools were the secondary comparison group. The trauma-checklist of the Current and Lifetime Version of the Kiddies Schedule for Affective Disorders and Schizophrenia was used as a guide in assessing traumatic events. Results: Of a total of 408 adolescents, 204 were recruited from the two juvenile justice institutions and 204 from secondary schools. Ninety per cent of participants were male and the mean (SD) age was 15·9 (2·8) years. The prevalence rate of lifetime exposure to traumatic events among the juvenile justice offenders was 88·7% compared with 48·5% of the comparison group ( P = 0·001). The most commonly reported specific lifetime traumatic event was physical abuse (52·8%). The institutionalised adolescents were significantly more likely to report lifetime exposure to almost all the traumatic events assessed. Apart from the perpetrators of violent crime, there was no statistically significant difference in the prevalence and pattern of lifetime exposure to traumatic events between the offenders and the victims. Conclusions: This study provides further evidence that exposure to traumatic events is a fact of life for inmates of juvenile institutions, irrespective of whether they are offenders or victims. The implications for reform of the Nigerian juvenile justice system are discussed.